👤

Calculati :

1) x³+3x²-x-3

2) [tex] x^{6} [/tex]  - [tex] x^{4} [/tex] - 16x²+16

3) x³-2x²-x+2

4) x³-x²-9x+9

5) x³+2x²-x-2

6) x³+3x²-4x-12

7) x³+3x²-9x-27


Răspuns :

[tex]1) $ $ x^3+3x^2-x-3= x^3-x+3x^2-3 = x(x^2-1)+3(x^2-1)= \\ \\ =(x^2-1)(x+3) = (x-1)(x+1)(x+3) \\ \\ \\2) $ $ x^6-x^4-16x^2+16 = x^4(x^2-1)-16(x^2-1) = \\ \\ = (x^2-1)(x^4-16) = (x-1)(x+1)(x^2-4)(x^2+4) = \\ \\ =(x-1)(x+1)(x-2)(x+2)(x^2+4) \\ \\ \\3) $ $ x^3-2x^2-x+2= x^3-x-2x^2+2 = x(x^2-1)-2(x^2-1)= \\ \\ =(x^2-1)(x-2) = (x-1)(x+1)(x-2) [/tex]


[tex]4) $ $ x^3-x^2-9x+9= x^2(x-1)-9(x-1) = (x-1)(x^2-9)= \\ \\ =(x-1)(x-3)(x+3) \\ \\ \\ 5) $ $ x^3+2x^2-x-2= x^3-x+2x^2-2 = x^2(x-1)+2(x^2-1) = \\ \\ =(x-1)(x^2+2) \\ \\ \\ 6) $ $ x^3+3x^2-4x-12 = x^3-4x+3x^2-12 = x(x^2-4)+3(x^2-4)= \\ \\ =(x+3)(x^2-4)= (x+3)(x-2)(x+2) \\ \\ \\ 7) $ $ x^3+3x^2-9x-27 = x^2(x+3)-9(x+3) = \\ \\ =(x+3)(x^2-9) = (x+3)(x-3)(x+3) = (x+3)^2\cdot (x-3)[/tex]
[tex]1) x^{3}+3x^{2}-x-3[/tex]
[tex]x\cdot(x^{2}-1)+3(x^{2}-1)[/tex]
[tex](x+3)\cdot(x^{2}-1)[/tex]
[tex](x+3)\cdot(x-1)\cdot(x+1)[/tex]

[tex]2) x^{6}-x^{4}-16x^{2}+16 \Rightarrow[/tex] Eşti sigur? Mai verifică! Mie nu îmi iese!

[tex]3)x^{3}-2x^{3}-x+2[/tex]
[tex]x\cdot(x^{2}-1)-2(x^{2}-1)[/tex]
[tex](x-2)\cdot(x^{2}-1)[/tex]
[tex](x-2)\cdot(x-1)\cdot(x+1)[/tex]

[tex]4)x^{3}-x^{2}-9x+9[/tex]
[tex]x^{2}\cdot(x-1)-9(x-1)[/tex]
[tex](x^{2}-9)\cdot(x-1)[/tex]
[tex](x-3)\cdot(x+3)\cdot(x-1)[/tex]

Mai departe fă tu.... eu nu mai am timp! Hai, că sunt simple!